KAITAN PEMBERITAAN PARA NABI DENGAN TAURAT, HIKMAT, DAN APOKALIPTIK DALAM PERJANJIAN LAMA - Elisamark Sitopu (Institut Agama Kristen Negeri Tarutung, 2018)
AbstractThis paper discusses the relation between the messages of the prophet with other literature in the bible. The messages from prophets, such as Jeremiah, Isiah related, to special parts in torah namely Covenant, exodus. Another parts is related to wisdom and Apocaliptic. It means we have to learn other parts of the bible in order to understand the messager of the prophetis.Keywords: Relation, message of the propetis, Literatur